The effect of pressure on transformation temperatures and some physical parameters of Fe-32Mn-6Si-3Cr shape memory alloy - Tatar, C; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2005)
An experimental investigation of the effect of pressure on shape memory behavior of Fe-32%Mn-6%Si-3%Cr alloy was undertaken. There are significant differences in the Gibbs free energy, dislocation density and transformation temperatures of the alloy due to applied pressure. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: shape memory alloy; stress; Gibbs free energy; dislocation density